Bacteria tolerant to colistin in coastal marine environment: Detection, microbiome diversity and antibiotic resistance genes' repertoire. (October 2021) - Šamanić, Ivica; Kalinić, Hrvoje; Fredotović, Željana; Dželalija, Mia; Bungur, Ana-Marija; Maravić, Ana
Abstract: The global spread of mobilized colistin resistance ( mcr ) genes in clinical and natural environments dangerously diminishes the effectiveness of this last-resort antibiotic, becoming an urgent health threat. We used a multidisciplinary approach to detect mcr-1 gene and colistin (CL)-resistant bacteria in seawater from two Croatian public beaches. Illumina-based sequencing of metagenomic 16S rRNA was used to assess the taxonomic, functional, and antibiotic resistance genes (ARGs) profiling of the bacterial community tolerant to CL regarding different culture-based isolation methodologies. Data revealed that the choice of methodology alters the diversity and abundance of taxa accounting for the CL-resistance phenotype. The mcr-1 gene was identified by cloning and sequencing in one sample, representing the first report of mcr-1 gene in Croatia. Culturing of CL-resistant strains revealed their resistance phenotypes and concurrent production of clinically significant β-lactamases, such as CTX-M-15, CTX-M-3 and SHV-12. We also report the first identification of bla CTX-M-15 gene in Klebsiella huaxiensis and K. michiganensis, as well as the bla TEM-1+CTX-M-3 in Serratia fonticola. ARGs profiles derived from metagenomic data and predicted by PICRUSt2, showed the highest abundance of genes encoding for multidrug efflux pumps, followed by the transporter genes accounting for the tetracycline, macrolide and phenicol resistance. Our study evidenced the multidrug resistance features of CL-tolerant bacterial communities thriving in surface beach waters. We also showed that combined application of the metagenomic approaches and culture-based techniques enabled successful detection of mcr-1 gene, which could be underreported in natural environment. Graphical abstract: Image 1 Highlights: Bacterial community tolerant to colistin from coastal public waters was surveyed. First identification of mcr-1 gene in Croatia. Taxonomic, functional and ARGs profiles assesed by Illumina-based sequencing. Highest abundance of multidrug efflux-related genes predicted by PICRUSt2. First report of bla CTX-M-15 gene in Klebsiella huaxiensis and K. michiganensis.